Long-term follow-up after transoral outlet reduction following Roux-en-Y gastric bypass: Back to stage 0? - Brunaldi, Vitor Ottoboni; Peixoto de Oliveira, Guilherme Henrique; Kerbage, Anthony; Ribas, Pedro Henrique; Nunes, Felipe; Faria, Galileu; de Moura, Diogo; Riccioppo, Daniel; Santo, Marco; de Moura, Eduardo (Endoscopy International Open, 2023)
Background and study aims Significant weight regain affects up to one-third of patients after Roux-en-Y gastric bypass (RYGB) and demands treatment. Transoral outlet reduction (TORe) with argon plasma coagulation (APC) alone or APC plus full-thickness suturing TORe (APC-FTS) is effective in the short term. However, no study has investigated the course of gastrojejunostomy (GJ) or quality of life (QOL) data after the first post-procedure year.Patients and methods Patients eligible for a 36-month follow-up visit after TORe underwent upper gastrointestinal endoscopy with measurement of the GJ and answered QOL questionnaires (RAND-36). The primary aim was to evaluate the long-term outcomes of TORe, including weight loss, QOL, and GJ anastomosis (GJA) size. Comparisons between APC and APC-FTS TORe were a secondary aim.Results Among 39 eligible patients, 29 returned for the 3-year follow-up visit. There were no significant differences in demographics between APC and APC-FTS TORe groups. At 3 years, patients from both groups regained all the weight lost at 12 months, and the GJ diameter was similar to the pre-procedure assessment. As to QOL, most improvements seen at 12 months were lost at 3 years, returning to pre-procedure levels. Only the energy/fatigue domain improvement was kept between the 1- and 3-year visits.Conclusions Obesity is a chronic relapsing disease. Most effects of TORe are lost at 3 years, and redilation of the GJA occurs. Therefore, TORe should be considered iterative rather than a one-off procedure.